A Review of the Epistemological Viewpoint of Mirza Mahdi Esfahani - Amir Ghorbani; Qader Hafez (حکمت اسرا)
A discussion of the epistemic foundations of a school of thought is, in effect, an attempt to explain the significance, realm, resources, method and logics of knowledge in that school of thought. In this regard, the Separation School, as one of the schools of thought in the history of Islamic thought, has a special epistemological foundation. Although this school of thought has been met by various differing interpretations and has undergone a number of modifications throughout history, the unchangeable emphasis of all its proponents have always been the necessity of making a distinction between the three sources of knowledge, i.e. the Quran (the revealed source), philosophy (the intellectual source), and mysticism (intuitive source) (Hakimi, 1996). This way, the proponents of the Separation school have sought to access religious and Quranic knowledge in its pure dorm and devoid of eclectic and interpreted matters (Hakimi, 1996). Thus, the source and the method of gaining the religious knowledge used by the Separation School are considered to be more genuine than the other two sources. In this regard, the ideas of Mirza Mahdi Esfahani, the founder of this school of thought, seem to be quite notable as they reflect a maximalist interpretation of the Separation approach. The present paper is an attempt to investigate this scholar’s epistemological principles.